Daydreaming - Zittoun, Tania; Mazourkova Cabra, Martina (Cham: Palgrave Maximilian, 2020)
Daydreaming can be defined as the process by which we partly or fully decouple from what seems to be one’s current activity in the world. It usually designates “anything one may be thinking about that does not pertain to the task in which one is currently involved” (Pereira and Diriwächter, 2008). Occurring within our flow of consciousness, it entails fantasy or a form of diurnal dreaming. Daydreaming can be more or less deliberate, have more or less clear goals, be more or less structured, and have diverse types of outcomes. Authors usually distinguish daydreams that may enrich people’s relation to themselves, or their relation to the world, from those which seem not to enrich experiences. Most authors admit that daydreaming participates to our capacity to deal with our experiences and opens up new possibilities.
Keywords: Daydreaming; Fantasy; Phantasy; Imagination; Mind-wandering; Singer; Freud; Lacan: Winnicott; Sociocultural psychology; Psychoanalysis